Pregnancy-associated plasma protein – a new biochemical marker of acute coronary syndrome and poor prognosis predictor in coronary heart disease patients - O. P. Shevchenko; A. O. Shevchenko; E. V. Kochetova; O. V. Orlova (Кардиоваскулярная терапия и профилактика)
Background. Pregnancy-associated plasma protein (PAPP-A) is Zn-containing proteinase, activating insulin-like growth factor. PAPP-A level increase is observed in acute coronary syndrome (ACS) and other inflammatory and destructive pathology. Aim. To investigate PAPP-A blood levels in patients with various forms of coronary heart disease (CHD), and their link to two-year prognosis. Material and methods. The study included 75 patients aged 62.3±10.1 years: 17 individuals with myocardial infarction (MI), 23 participants with unstable angina (UA), 24 patients with effort angina, and 11 healthy volunteers. The follow-up lasted for two years. End-points (EP) included death, MI, UA, and heart failure (HF) progression. Besides routine clinical tests, the levels of PAPP-A, interleukin-6 (IL-6), and C-reactive protein (CRP) were measured by highly sensitive immuno-enzyme methods. Results. PAPP-A levels significantly correlated with CRP (r=0.361; р=0.043) and IL-6 concentration (r=0.387; р=0.035). PAPP-A, IL-6, and CRP blood levels were similar in healthy volunteers and SA patients. Comparing to SA patients, UA participants had increased levels of PAPP-A (8.6±6.7 vs 14.4±9.5 mIU/l; p<0.05) and CRP (4.5±4.0 vs 7.3±5.5 mg/l; p<0.05). In CHD patients with PAPP-A level <10 mIU/l (n=32), EP were registered in 4 cases. Among patients with PAPP-A levels >10 mIU/l (n=32), EP were registered in 11 participants. Mean time till EP registration was 1030±52 and 656±51 days, respectively (p<0.05). Comparing EP-free survival (logrange method), it was demonstrated that prognosis was better in subjects with PAPP-A levels <10 mIU/l, than in participants with PAPP-A levels >10 mIU/l (p=0.047). Conclusion. PAPP-A is a marker participating in CHD pathogenesis. Its blood levels correlated with systemic inflammation severity, being elevated in ACS patients. Patients with higher PAPP-A levels had poorer prognosis.